Prognostic value of baseline interleukin 6 levels in liver decompensation and survival in HCC patients undergoing radioembolization - Osman Öcal; Juozas Kupčinskas; Egidijus Morkunas; Holger Amthauer; Kerstin Schütte; Peter Malfertheiner; Heinz Josef Klümpen; Christian Sengel; Julia Benckert; Ricarda Seidensticker; Bruno Sangro; Moritz Wildgruber; et al. (EJNMMI Research, 2021)
Abstract Background To confirm the prognostic value of previously published baseline interleukin 6 (IL6) and IL8 cutoff values in survival and liver dysfunction in patients with advanced HCC undergoing 90Y radioembolization. Methods A total of 83 patients (77 male) represented a subset of HCC patients undergoing 90Y radioembolization combined with sorafenib as part of the prospective multicenter phase II trial SORAMIC. IL6 and IL8 levels were determined in serum samples collected at baseline. In this post hoc analysis, we sought to confirm the prognostic value of baseline cutoff values of 6.53 pg/mL and 60.8 pg/mL for IL6 and IL8, respectively, in overall survival (OS) or liver dysfunction (grade 2 bilirubin increase) after treatment. Results Median OS was 12.0 months. While low baseline albumin and high bilirubin values were associated with high IL6, liver cirrhosis, alcoholic liver disease, and portal vein infiltration were associated with high IL8. In univariate analysis, high baseline IL6 and IL8 were associated with significantly shorter overall survival (7.8 vs. 19.0 months for IL6 and 8.4 vs. 16.0 months for IL8). In addition to IL values, liver cirrhosis, Child–Pugh grade, baseline albumin (< 36 g/dL), and total bilirubin (≥ 17 µmol/L), and higher mALBI grade (2b &3) values were associated with OS. At multivariate analysis, high baseline IL6 was the only independent prognostic factor for OS (HR 2.35 [1.35–4.1], p = 0.002). Risk factors for liver dysfunction were high baseline IL6, albumin, and total bilirubin, and mALBI grade as found in univariate analysis. High baseline IL6 (HR 2.67 [1.21–5.94], p = 0.016) and total bilirubin ≥ 17 µmol/L (HR 3.73 [1.72–8.06], p < 0.001) were independently associated with liver dysfunction. Conclusion In advanced HCC patients receiving 90Y radioembolization combined with sorafenib, baseline IL6 values proved to be prognostic, confirming previous findings in patients undergoing 90Yradioembolization. IL6 might be useful for patient selection or stratification in future trials.